2014
DOI: 10.1111/jhn.12222
|View full text |Cite
|
Sign up to set email alerts
|

Prompted awareness and use of Eating Well with Canada's Food Guide: a population‐based study

Abstract: Sex, ethnicity and income were associated with general awareness of CFG. Future studies could explore the relationship between awareness and other health-related behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Previous research has documented very low utilization of CFG in several groups across Canada, and non-Caucasian ethnic origin is a risk factor for low awareness of CFG (Jacobs Starkey, Johnson-Down, & Gray-Donald, 2001;Mathe et al, 2015). In our sample, most of the Tamil participants are no exception.…”
Section: Exposure To Canada's Food Guidementioning
confidence: 64%
“…Previous research has documented very low utilization of CFG in several groups across Canada, and non-Caucasian ethnic origin is a risk factor for low awareness of CFG (Jacobs Starkey, Johnson-Down, & Gray-Donald, 2001;Mathe et al, 2015). In our sample, most of the Tamil participants are no exception.…”
Section: Exposure To Canada's Food Guidementioning
confidence: 64%
“…This tool is intended for healthy Canadians and is readily available to the population, particularly in schools. Most Canadians (86·5 %) report having general awareness of CFG ( 15 ) . For the design of a questionnaire related to CFG recommendations, specific items were required.…”
mentioning
confidence: 99%
“…This is similar to previous survey research which found that awareness of the 2019 CFG was high among Canadian adults (Charlebois et al, 2021). Awareness of the 2007 CFG has also shown to be high with over 80% of Canadian adults stating they have heard of the 2007 Food Guide (Slater & Mudryj, 2018).While awareness of the CFG is high, this awareness does not appear to translate into Canadians meeting the dietary recommendations promoted in the CFG (Mathe et al, 2015;Slater & Mudryj, 2018;Vanderlee et al, 2015). The current findings regarding parents' perceptions of CFG and challenges in meeting the CFG may help explain this gap.…”
Section: Discussionmentioning
confidence: 76%